Sport, mental illness, and sociology - Atkinson, Michael, 1971- (Research in the sociology of sport ;, 2018)
At a time when the public discussion of mental illness in society is reaching a highpoint, athletes and other sports insiders remain curiously silent about their private battles with a range of mental illnesses. While a series of professional athletes have exposed the deep, dark secret related to the pervasiveness of mental illness in high performance sport, relatively little is known, sociologically, about what mental illness culturally means inside sport. This edited collection showcases research on how sport, as a social institution, may actually produce dangerous cultural practices and contexts that foster the development of mental illness within athlete groups. Further, chapters also illustrate how sport, when organized with sensitivity and care, may serve to help manage mental illnesses. Rather than analyzing mental illness as an individual phenomenon, contributors to this volume equally attest to how mental illness is socially developed, constructed, managed, and culturally understood within sport settings. The book highlights the relevance of a range of theories pertinent to the social study of mental illness including dramaturgy, cultural studies, learning theory, symbolic interaction, existentialism, and total pain theory. Chapters range from the discussion of depression, anxiety, eating disorders, drug addiction, epilepsy, mental trauma, stigma, the mass mediationof mental illness, and the promise of sport as a vehicle for personal and collective recovery.